Value Co-Creation in Telemedicine: A Qualitative Study of Pediatricians’ Expectations Regarding Telehomecare Implementation in an Italian Pediatric Hospital - Bernuzzi C; Piccardo MA; Marsilio M; Calcaterra V; Zuccotti G; Guglielmetti C (Dove Medical Press, 2024)
Chiara Bernuzzi,1 Maria Adele Piccardo,1 Marta Marsilio,2 Valeria Calcaterra,3,4 Gianvincenzo Zuccotti,2,3 Chiara Guglielmetti1 1Department of Economics, Management and Quantitative Methods (DEMM), University of Milan, Milan, 20122, Italy; 2Department of Biomedical and Clinical Science, University of Milan, Milan, 20157, Italy; 3Pediatric Department, Buzzi Children's Hospital, Milan, 20154, Italy; 4Department of Internal Medicine, University of Pavia, Pavia, 27100, ItalyCorrespondence: Chiara Bernuzzi, Department of Economics, Management and Quantitative Methods (DEMM), University of Milan, via Conservatorio, 7, Milan, 20122, Italy, Email chiara.bernuzzi@unimi.itPurpose: The widespread adoption of telemedicine tools poses new and little-known challenges for healthcare professionals, who are required to adapt their knowledge, skills, and work practices to this innovative scenario. Understanding healthcare professionals' expectations and concerns about adopting telemedicine can facilitate its effective integration. Therefore, drawing upon the Value Co-Creation in Healthcare model, the current study aims to investigate pediatricians' expectations regarding antecedents, outcomes, and management activities relevant to the implementation of a telehomecare service.Methods: Interviews invitations were sent to all pediatricians (n=13) involved in a pilot study using the TytoCare device, a telehomecare tool that enables remote medical examinations, at an Italian pediatric hospital. All invited pediatricians agreed to participate. The semi-structured interviews, each lasting approximately 30 to 45 minutes, were conducted remotely via Microsoft Teams prior to the use of the TytoCare device. All interviews were recorded and transcribed verbatim. The content was subsequently analyzed through thematic analysis using MAXQDA software.Results: Five overarching thematic areas emerged from the interviews: factors influencing the adoption of the telehomecare device, advantages of its use, impacts on work practices, changes in the patient-professional relationship, and management activities. While concerns exist about the adequacy of telehomecare compared to in-person visits, the device offers potential benefits, such as improving the hospital experience for children by shortening hospital stays. However, it may lead to an increased workload and necessitate stronger trust and communication in remote care. Successful integration requires dedicated support staff, regulatory adjustments, and effective leadership, with active involvement of healthcare professionals in decision-making.Conclusion: By shedding light on healthcare professionals' expectations about telehomecare device, this study provides useful insights to healthcare leaders to tailor interventions to accompany technology within care practices to valorize its benefits and promote value co-creation processes.Keywords: telehomecare, expectations about telemedicine, pediatricians, healthcare professionals, co-creation of value, qualitative